Strategi Mitigasi Risiko Pada Penyelenggaraan Maybank Marathon Bali 2024 Oleh CV. Kopi Panas - Napitupulu, Kesya Cella Petrecya; Wirata, I Nengah; Widaharthana, I Putu Esa (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This research analyzes the risk mitigation strategies implemented by the Program Division of CV. Kopi Panas in organizing the Maybank Marathon Bali 2024, focusing on key event programs (Main Stage, Maybank Interactive Lounge, and Sustainability Pavilion). Using a qualitative approach, the study employed in-depth interviews, observations, and documentation analysis. Framed within the ISO 31000:2018 risk management standard, the findings identified critical risks including last-minute schedule changes, technical disruptions, and low participant engagement. Effective mitigation measures involved implementing backup operational procedures, staff training programs, and enhanced coordination protocols. The study demonstrates that a structured, collaborative approach significantly reduces operational risks. Practical recommendations emphasize workforce capacity building and real-time monitoring technologies, contributing both to event management practices and sport tourism risk management literature.